Secure and sustainable food processing supply chain framework based on Hyperledger Fabric technology - Mosiur Rahaman; Farhin Tabassum; Varsha Arya; Ritika Bansal (Cyber Security and Applications)
Food processing supply chains are gradually facing the problem of incorporation and sustainability because of the complexity of many participants involved in the supply chain network. Customers are very aware of and particularly interested in the quality, safety, and provenance of food processing products. However, conventional supply chains, on the other hand, rely heavily on a third party for transactions and confidence. Traditional supply chain models only partially reveal information about an organization to other parties, which results in inadequate data and a communication gap. Although emails and printed papers offer some information, the capacity to provide utterly accurate visibility and traceability information is impossible since the items throughout the supply chain are difficult to trace. In this research, we provide a fully distributed method, Hyperledger Fabric, to establish a food processing supply chain system incorporating a Hyperledger Fabric framework designed to demonstrate the efficiency of the approach and analyze the main use cases needed in a food processing supply chain network.